Experimental Research on an Active Sting Damper in a Low Speed Acoustic Wind Tunnel - Jinjin Chen; Xing Shen; Fanfan Tu; Ehtesham Mustafa Qureshi (Shock and Vibration)
Wind tunnels usually use long cantilever stings to support aerodynamic models in order to reduce support system flow interference on experimental data. However, such support systems are a potential source of vibration problems which limit the test envelope and affect data quality due to the inherently low structural damping of the systems. When exposed to tunnel flow, turbulence and model flow separation excite resonant Eigenmodes of a sting structure causing large vibrations due to low damping. This paper details the development and experimental evaluation of an active damping system using piezoelectric devices with balance signal feedback both in a lab and a low speed acoustic wind tunnel and presents the control algorithm verification tests with a simple cantilever beam. It is shown that the active damper, controlled separately by both PID and BP neural network, has effectively attenuated the vibration. For sting mode only, 95% reduction of displacement response under exciter stimulation and 98% energy elimination of sting mode frequency have been achieved.